Systematic review about methods of energy expenditure and energy intake in children and adolescents - Francisco de Assis Guedes de Vasconcelos; Fernando Adami; Deivis Elton Schilickmann Frainer (Universidade Federal de Santa Catarina, 2008)
The objective of this systematic review was to identify, describe and analyze methods used for determining energy expenditure and energy intake in clinical and population-based epidemiological studies. The study population was made up of children and adolescents aged from 6 to 18 years. The articles were identifi ed by means of searching the Medline database. A total of 141 articles were identifi ed, 32 of which were selected. From these, 10 articles were chosen, 6 of which were clinical epidemiological studies and 4 were populational epidemiological studies. The methods used to determine energy expenditure in the clinical studies were doubly labeled water and indirect calorimetry. In the populational studies, questionnaires on physical activity were used to determine the energy expended during physical activity. The methods used to evaluate nutritional intake, both in the clinical and populational epidemiological studies, were 24-hour dietary recalls, food records and food frequency questionnaires. The review goes on to discuss questions such as the manner in which these methods are employed and their validation and adaptation for populations of children and adolescents. It is concluded that care must be taken with the methodological aspects of epidemiological study design in order to avoid introducing bias to results and limiting conclusions. Resumo O objetivo dessa revisão sistemática foi identifi car, descrever e analisar os métodos de determinação do gasto e consumo energéticos em estudos epidemiológicos clínicos e populacionais. A população do estudo foi de crianças e adolescentes na faixa etária de 6 a 18 anos. Para isso, foi realizada uma busca na base de dados Medline. Foram encontrados 141 artigos, dos quais 32 foram selecionados. Desses, foram obtidos 10 artigos, sendo 6 estudos de epidemiologia clínica e 4 de epidemiologia populacional. Nos estudos de epidemiologia clínica, os métodos usados para a determinação do gasto energético foram água duplamente marcada e calorimetria indireta. Nos estudos de epidemiologia populacional, o questionário de atividade física foi utilizado para determinação do gasto energético com atividade física. Os métodos de avaliação do consumo alimentar utilizados, tanto em epidemiologia clínica quanto em populacional, foram recordatório de 24 horas, registro alimentar e questionário de freqüência alimentar. São discutidas questões como a forma de realização dos métodos, a validação e adaptações para a população de crianças e adolescentes. Conclui-se que cuidados metodológicos devem ter maior apreço no design dos estudos epidemiológicos, pois podem enviesar os resultados e limitar conclusões.